Black Men and the Digital Divide. Issue 150 (June 2016) - Conceição, Simone C. O.; Martin, Larry G.
Abstract : This chapter focuses on the role adult educators can play in assisting Black men to overcome the challenges faced in accessing and using digital technology and acquiring appropriate skills in a digital society.